Botanical Gardens, Trinidad, B.W.I. - No. 46 - (:unkn) unknown (Muir, Marshall and Co., 2009)
A picture of a man standing on a path in the Botanical Gardens that is lined with tall Palm trees. Affixed to the back of the postcard is a Trinidad and Tobago 1 penny stamp.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Men--Trinidad and Tobago